Bilateral Corneal Arcus In Canine - Ramos, Lais Caroline Gomes; Cunha, Tiago Oliveira; Nascimento, Gustavo De Oliveira; Leite, Lylian Theresa Belizário; Gomes, Luedja Carla Vidal Monteiro; de Souza, Almir Pereira (Acta Scientiae Veterinariae, 2020)
Background: The cornea is a component of the animal’s eye that is transparent in appearance because of the arrangement of collagen fibrils and the absence of vascularization and pigmentation. Corneal degeneration can result in a lesion known as corneal arcus, which presents as loss of transparency. It is characterized by a dense white opacity with defined borders. This lesion can be caused by lipid keratopathy, occurring as cholesterol and triglyceride deposits in the corneal stroma. In this case, analysis of the serum lipid profile and evaluation of thyroid and pancreas function are recommended. This study aimed to report on a case of occurrence of corneal arcus in a canine. Case: A 6-year-old dog, of no defined breed, weighing 13.250 kg was attended at the Veterinary Hospital of the Universidade Federal de Alagoas with a 5-day history of constipation. Under ultrasound, fecaloma was observed; however, the finding that drew attention was the presence of an eye alteration presenting as bilateral opacity in the form of a vertical arc in the corneal regions, with whitish crystalline appearance. The lesion did not exhibit roughness or vascularization and had well-defined borders. The animal showed no discomfort or visual acuity changes. The tutor reported that the marks had already been on the animal’s eye when it was adopted four years age, and that it showed a slow progressive growth. Given that there were no clinical signs of metabolic or hormonal diseases that could be a primary cause for the formation of the corneal lesion, lipid or calcium deposition in the corneal stroma was suspected, possibly due to diet or idiopathic cause. Blood samples were collected for a blood count and to determine triglyceride, calcium, and cholesterol levels. Based on the test results (all within the normal range), history, and a physical examination (with no evidence of metabolic and/or endocrine diseases), a diagnosis of corneal arcus was made. Excessive lipids in the diet was suggested as the cause of lesions, given that the dog’s diet had consisted of rice with a beef broth tablet, once a day, which over the years may have contributed to both the formation of the corneal lesions and to the enteric disorder (fecaloma). Dietary correction was indicated for both disorders, consisting of commercial dog food of adequate nutritional value. Keratectomy was not indicated for the corneal lesions, as they did not appear to be compromising the field of vision. Instead, we opted for follow-up to monitor the growth of lesions. Discussion: As no clinical evidence of metabolic or hormonal disease was verified, the primary cause for the formation of the corneal lesions was assumed to be lipid or calcium deposits in the corneal stroma, due to diet or even idiopathic cause. The dog was fed boiled rice and industrialized meat broth tablet, providing inadequate nutrition for the past four years or so, possibly leading to hyperlipidemia and/or hypercalcemia, with consequent deposition in the cornea, causing the arc lesion. Triglyceride, cholesterol, and calcium levels were measured, and were within normal range, probably because the blood collection was performed after the control of the post-enterotomy diet. Therefore, it was not possible to correlate the corneal changes with hyperlipidemia or hypercalcemia. The animal did not present with impaired vision as the lesions were located in the peripheral regions of the cornea, bilaterally. Therefore, it was decided to not to perform keratectomy.